Pendekatan Pembelajaran Berbasis Self Directed Learning dalam Membangun Kemampuan Literasi Matematika - Syihada, Ghefira Nur; Sugilar, Hamdan; Ihsan, Muhammad (Science, Tecnology, Religious, Economic, and Social Humanitis (STREAS), 2025)
This research aims to examine the role of Self-Directed Learning (SDL) based learning models in encouraging students' mathematical literacy skills. The SDL learning model aims to give students the ability to become independent and skilled learners in understanding, analyzing and solving mathematical problems in various situations. This research adopts a Systematic Literature Review (SLR) approach, which follows a series of systematic steps to collect, review and analyze scientific literature related to the research discussion, namely regarding Self Directed Learning (SDL) based learning methods and mathematical literacy skills. These findings show how well the SDL-based learning model works to improve student learning outcomes in mathematics. Students who use SDL in their math classes report being more motivated, independent, and having a deeper understanding of the material. In addition, SDL can support the growth of students' mathematical literacy skills, including reasoning, problem solving, communication, and the use of mathematical instruments. One of the efficient substitute learning models for increasing students' mathematical literacy levels is the SDL-based learning model. Students can be successful in their education and life by using the Self-Directed Learning learning model in teaching mathematics effectively